Hubungan Pemberian Pisang Ambon Dengan Kadar Hemoglobin Pada Ibu Hamil Trimester I Dengan Anemia Ringan Di Tpmb Susi Di Dolok Merawan Kabupaten Serdang Bedagai - Friska Sinaga; Erlin Novitasari; Maya Primayanti (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Anemia in pregnancy is characterized by a condition in which the body has few red blood cells or the cells cannot carry oxygen throughout the body. it is estimated that the prevalence of anemia in pregnant women in Indonesia in 2019 is 48.9%. Bananas are the best food because they contain vitamins needed by pregnant women. Bananas are sufficient to meet the substance intake of anemic patients. The aim of the study was to determine the relationship between Ambon Banana Administration and Hemoglobin Levels in Pregnant Women with Mild Anemia in the First Trimester. This research was carried out using quantitative analytic research with a cross sectional approach by collecting secondary data from medical records. from April 2021 to June 2022 . This research was conducted at TPMB Susi in Dolok Merawan District, Serdang Bedagai Regency in February 2023. The sampling technique used total sampling with a total sample of 42 pregnant women in the first trimester with mild anemia who met the inclusion and exclusion criteria. Analysis using the Chi Square statistical test shows that the p value is 0.000 (<0.05). So that the hypothesis can be accepted, then there is a "Relationship between Giving Ambon Bananas and Hemoglobin Levels in Pregnant Women with Mild Anemia in the First Trimester. The results of this study indicate that there is a relationship between giving Ambon bananas and hemoglobin levels of pregnant women after being given Ambon bananas. Giving ambon bananas can be suggested as an alternative complement of vitamins to increase hemoglobin levels.